Morphometric Analysis of the Rawandoz River Basin, Erbil, Kurdistan Region, Iraq - Shevan Jirjees; Shwan Seeyan; Imaddadin Hassan (Iraqi Geological Journal, 2022)
In this research detailed morphometric investigation of the Rawanduz river basin in the northeastern part of Erbil, Iraq has been made. The study area covers an approximately 977.68 km2. Digital Elevation Model data (DEM 12.5 m), Remote sensing and GIS methods were used for studying basin morphometric parameter such as linear, aerial, and relief aspects, as well as to delineate lineaments in the study area.The results reveal that there is an opposite correlation between stream order, stream number, and length of streams in the research region basin by R2 values (R2 = 0.77 and 0.73) which is good value depending on statistical analysis. Streams were also ordered, with a total of 6376 streams totaling 2376.4 km in length. The basin's elongation ratio (0.54), circulation ratio (0.45), and form factor (0.23) data suggested that it was semi-elongated to elongated in nature, with poor permeability material, high relief, steep slopes, and main drainage pattern types affected by lineaments and fracture traces. In the research region, the stream frequency value is 5.6 km2 which is a high value suggesting impermeable lithology and enhanced surface runoff in the basin area. The drainage density in the investigated area is 2.43 km-1. The Rawanduz river basin's high drainage density value (2.43 km-1) reveals a fine drainage texture value (38.77 km-3). This study will help decision-makers and local residents to benefit from the resources for the sustainable development of the basin area.